Ministry Of Planning and Economic Development Decree No. 6 Of The Year 2022 = وزارة التخطيط والتنمية الاقتصادية قرار رقم 6 لسنة 2022 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic